Experience of using a cultural circle meeting as a reference for educational intervention with adolescents (Research, Society and Development, 2020)
The article aims to report the experience of an educational intervention with adolescents, based on the methodology of Paulo Freire of a Cultural Circle Meeting, as a method of educating and promoting health, in the context of drug use. The interventions were performed in a public high-school in the city of Sobral, Ceará, Brazil; between the months of August 2013 to March 2014, with 121 adolescents. The undertaking and amassment of adolescents talking about drug use, gained momentum with the implementation of the five steps of the Cultural Circle Meeting, by using the methodology of dialog and participation, facilitated the roles of the subjects of building knowledge closer to their reality and needs.